If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -1 + -17y = -20 + -15y Combine like terms: 19 + -1 = 18 18 + -17y = -20 + -15y Solving 18 + -17y = -20 + -15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '15y' to each side of the equation. 18 + -17y + 15y = -20 + -15y + 15y Combine like terms: -17y + 15y = -2y 18 + -2y = -20 + -15y + 15y Combine like terms: -15y + 15y = 0 18 + -2y = -20 + 0 18 + -2y = -20 Add '-18' to each side of the equation. 18 + -18 + -2y = -20 + -18 Combine like terms: 18 + -18 = 0 0 + -2y = -20 + -18 -2y = -20 + -18 Combine like terms: -20 + -18 = -38 -2y = -38 Divide each side by '-2'. y = 19 Simplifying y = 19
| 5y+15=34 | | 25x+7Y-7= | | 7x-9=2x+5 | | -4=-x+3 | | p=3+2p | | x/15-7=-2 | | -2n-23=4n+37 | | 3-5x-1/10=x-1/5-x-3/2 | | 1/3-1/8= | | X+8=-5x+20 | | t-5=-7+3t | | 20z-33=40 | | 4(2x+4)+2(3x-5)= | | 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 | | -4f+5=f+9f+5 | | x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 |